Insan Kamil dalam Keteladanan Rasulullah Saw.: Sebuah Kajian Hadis Tematik - Muhammad Lukman Firdaus (Jurnal Penelitian Ilmu Ushuluddin, 2022)
This research is motivated by the phenomenon of human morality which is increasingly worrying. The purpose of this study is to discuss the greatness of the morals of the Prophet Muhammad through thematic hadiths related to the theme of Insan Kamil. This research is a type of qualitative research through literature study with thematic hadith approach. The results and discussion of this study lead to the nature and behavior of the Prophet Muhammad as a perfect human proof that must be followed by the believer. The development of the Insan Kamil theme includes indicators of Insan Kamil, including the role of humans as caliph, physically and spiritually healthy, amar nahi munkar, and the peak is morality. This study concludes that the hadiths narrated by Imam Muslim related to insan kamil accompanied by thematic syarah are understood to be a reference for a person to shape himself into insan kamil in order to reach the pleasure of Allah SWT.